Living mycelium composites discern weights via patterns of electrical activity - Andrew Adamatzky; Antoni Gandia (Journal of Bioresources and Bioproducts, 2022)
Fungal construction materials—substrates colonised by mycelium—are getting increased recognition as viable ecologically friendly alternatives to conventional building materials. A functionality of the constructions made from fungal materials would be enriched if blocks with living mycelium, known for their ability to respond to chemical, optical and tactile stimuli, were inserted. We investigated how large blocks of substrates colonised with mycelium of Ganoderma resinaceum responded to stimulation with heavy weights. We analysed details of the electrical responses to the stimulation with weights and show that ON and OFF stimuli can be discriminated by the living mycelium composites and that a habituation to the stimulation occurs. Novelty of the results cast in the reporting on changes in electrical spiking activity of mycelium bound composites in response to a heavy loads.